2020
DOI: 10.1016/j.jds.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional training after orthognathic surgery on masticatory function in patients with mandibular prognathism

Abstract: Background/purpose Even after surgical orthodontic treatment, the level of masticatory function in patients with jaw deformities is still lower than that of healthy subjects. The purpose of this study was to evaluate the effects of functional training program using gum chewing exercise after orthognathic surgery on masticatory function in patients with mandibular prognathism. Materials and methods The study subjects were 16 patients with mandibular prognathism who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Finally, according to the recorded postoperative EMG activity in this study, improvement in the masticatory muscles' activity has been detected. This result was in acceptance with kawai et al (14) ., 2020, who reported the occurrence of marked improvement in the activity of masticatory muscles after correction of the present skeletal deformity.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, according to the recorded postoperative EMG activity in this study, improvement in the masticatory muscles' activity has been detected. This result was in acceptance with kawai et al (14) ., 2020, who reported the occurrence of marked improvement in the activity of masticatory muscles after correction of the present skeletal deformity.…”
Section: Discussionsupporting
confidence: 89%
“…If the patients have problems performing the lateral movement during mastication, the observation of the masticatory correct pattern focusing in the affected side will help to improve the cortical representation of the movement (Figure 7). The training will start with a duration of minutes, until the pattern of the movement cannot be performed correctly due to fatigue, and increased progressively until no more than 6 min of mastication, alternating sides after each minute [183].…”
Section: Masticatory Trainingmentioning
confidence: 99%
“…changes (see Figure5where 'anteroposterior change' = 0 mm).The effects of changes in mechanobehaviour on the TMJ mechanical environment post-surgically need consideration of the frequency of post-surgical mandibular loading. Studies have reported restoration of normal or near-normal function post-surgery in terms of occlusal contacts, maximum bite force, masticatory efficiency and neurosensory recovery [34][35][36]. Protracted disturbances in dynamic measures of jaw tracking may reflect the period of recovery required to develop neural templates of jaw movement.…”
mentioning
confidence: 99%